A case of Lynch syndrome diagnosed by microsatellite instability test performed as universal screening - Sekine, Shigeki; Kobatake, Takaya; Kobayashi, Naruyuki; Matsuyama, Yumi; Sugano, Kokichi; Hori, Shinichiro; Ochiai, Ryoji; Okamura, Miki; Teramoto, Norihiro; Ohsumi, Shozo; Kaneko, Keika (JOURNAL OF FAMILIAL TUMORS, 2019)
A 56-year-old male was admitted for surgery for transverse colon cancer. The patient had no paternal family history because his father died in an accident in his 40s. The patient underwent right hemi-colectomy. The histological diagnosis was moderately differentiated tubular adenocarcinoma （tub2>por1）, pT2pN0cM0 pStage I （Japanese Classification of Colorectal Carcinoma, 8th edition）. Microsatellite instability （MSI） test demonstrated the tumor to be MSI-High. Genetic testing revealed a pathogenic mutation in MSH6 and Lynch syndrome was diagnosed. Although the patient did not meet the Amsterdam Criteria II or the revised Bethesda guidelines, universal screening by MSI test led to the diagnosis of Lynch syndrome. Universal screening is useful to identify potential Lynch syndrome patients.